2015
DOI: 10.1152/ajpcell.00224.2015
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of gastric acid secretion by rabbit parietal cell A2B adenosine receptor activation

Abstract: Adenosine modulates different functional activities in many cells of the gastrointestinal tract; some of them are believed to be mediated by interaction with its four G protein-coupled receptors. The renewed interest in the adenosine A2B receptor (A2BR) subtype can be traced by studies in which the introduction of new genetic and chemical tools has widened the pharmacological and structural knowledge of this receptor as well as its potential therapeutic use in cancer and inflammation- or hypoxia-related pathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…Our study demonstrated that, in rabbits, the gastric parietal cell is endowed with a density of A2B receptors sufficient to promote acid secretion even though the affinity constants were similar to those reported in other tissues and cell models (Klotz et al, 1998 ; Fredholm et al, 2001b , 2011 ). We also demonstrated that such activation was mediated by a cAMP rise and not by calcium (Arin et al, 2015b ). In human crypt epithelial cells, activation of A2B receptor by adenosine promotes Cl − secretion via intracellular cAMP increase (Antonioli et al, 2008 ).…”
Section: Extracellular Adenosine: Sources and Receptorsmentioning
confidence: 62%
See 4 more Smart Citations
“…Our study demonstrated that, in rabbits, the gastric parietal cell is endowed with a density of A2B receptors sufficient to promote acid secretion even though the affinity constants were similar to those reported in other tissues and cell models (Klotz et al, 1998 ; Fredholm et al, 2001b , 2011 ). We also demonstrated that such activation was mediated by a cAMP rise and not by calcium (Arin et al, 2015b ). In human crypt epithelial cells, activation of A2B receptor by adenosine promotes Cl − secretion via intracellular cAMP increase (Antonioli et al, 2008 ).…”
Section: Extracellular Adenosine: Sources and Receptorsmentioning
confidence: 62%
“…In a bimodal response, ATP would act first on P2 receptors inducing ACh and ATP co-release (Vieira et al, 2009 ) and the enzymatically generated adenosine would induce or reduce ACh release upon binding to A2A or A1 receptor, respectively (Duarte-Araujo et al, 2009 ). The fact that gastric parietal cells and D cells express A2B (Arin et al, 2015a , b ) and A2A (Yip et al, 2004a ), respectively, suggests that adenosine is a bona fide extracellular mediator in the neighborhood; it is possible, therefore, to speculate that the autocrine regulation described above for myenteric neurons might operate too in the cholinergic fibers of the ENS innervating both parietal and D cells, representing an additional regulatory mechanism for adenosine in gastric acid secretion.…”
Section: Extracellular Adenosine: Sources and Receptorsmentioning
confidence: 99%
See 3 more Smart Citations